Healthy diet in the Amazon with nutrients and bioactive substances from tropical fruits (Research, Society and Development, 2022)
This work aims to contextualize, through a review of the literature, the importance of nutrients and bioactive substances present in the most consumed tropical fruits in the Amazon, and mainly, to emphasize the consumption of these fruits for a healthy diet. The objective of this work was to analyze the contribution of some tropical fruits in the supply of nutrients and bioactive substances and to relate their form of consumption to obtain a healthy and beneficial diet for human health. The literature review was conducted in 2022, based on articles, books, book chapters, dissertations and theses. The results showed that the consumption of fruits in the form of juices, particularly in collective feeding systems, contributes nutrients and bioactive substances to a healthy diet and positive health effects. In addition to nutrients, carotenoids, vitamin C and antioxidants are the main substances provided by fruits. The main fruits consumed in a healthy diet are pineapple, açaí, acerola, buriti, guava, mango, papaya, passion fruit, watermelon, peach palm and tucumã. These fruits are the most consumed, due to the affordable price, availability with harvest during a long period of the year, eating habits and greater acceptance by the population. The results indicated that encouraging the regular consumption of fruits should serve as a basis for the development of food and nutrition surveillance strategies, with the aim of promoting healthy eating habits.